An evolutionary genomic approach reveals both conserved and species-specific genetic elements related to human disease in closely related Aspergillus fungi. Issue 2 (4th May 2021) - Mead, Matthew E; Steenwyk, Jacob L; Silva, Lilian P; de Castro, Patrícia A; Saeed, Nauman; Hillmann, Falk; Goldman, Gustavo H; Rokas, Antonis
Abstract: Aspergillosis is an important opportunistic human disease caused by filamentous fungi in the genus Aspergillus . Roughly 70% of infections are caused by Aspergillus fumigatus, with the rest stemming from approximately a dozen other Aspergillus species. Several of these pathogens are closely related to A. fumigatus and belong in the same taxonomic section, section Fumigati . Pathogenic species are frequently most closely related to nonpathogenic ones, suggesting Aspergillus pathogenicity evolved multiple times independently. To understand the repeated evolution of Aspergillus pathogenicity, we performed comparative genomic analyses on 18 strains from 13 species, including 8 species in section Fumigati, which aimed to identify genes, both ones previously connected to virulence as well as ones never before implicated, whose evolution differs between pathogens and nonpathogens. We found that most genes were present in all species, including approximately half of those previously connected to virulence, but a few genes were section- or species-specific. Evolutionary rate analyses identified over 1700 genes whose evolutionary rate differed between pathogens and nonpathogens and dozens of genes whose rates differed between specific pathogens and the rest of the taxa. Functional testing of deletion mutants of 17 transcription factor-encoding genes whose evolution differed between pathogens and nonpathogens identified eight genes that affect either fungal survival in a model of phagocytic killing, host survival in an animal model of fungal disease, or both. These results suggest that the evolution of pathogenicity in Aspergillus involved both conserved and species-specific genetic elements, illustrating how an evolutionary genomic approach informs the study of fungal disease.